Real-time cheat-free gaming on the basis of time-stamp service - Mogaki, Shunsuke; Kamada, Masaru; Yonekura, Tatsuhiro; Okamoto, Shusuke; Otaki, Yasuhiro; Ibne Reaz, Md Mamun (IJCSNS, 2009)
A cheat-proof protocol for real-time gaming is proposed under the assumption that time-stamp servers issue serially numbered time stamps honestly and are available near every player, i.e., they exist everywhere in the Internet. With this protocol, each player sends its action to the other player and also sends its hash to the nearest time-stamp server. The time-stamp server sends the signed hash with the time and a serial number back to the player. The actions are checked to verify that they are compatible with the hashes, and the signed hashes are checked to verify that they have the correct time and the serial numbers are contiguous. The only latency in this protocol is the travel time of the packet from one player to another. In comparison with other existing protocols, we confirm that the proposed protocol is as fast as and more secure than the fair synchronization protocol, the fastest existing protocol